(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Online learning during the pandemic of Covid-19 affects the learning process in higher education. This research aimed at investigating the efficacy of flipped classroom model integrated with the online learning platform (by zoom meeting) and video biomechanics analysis to enhance the learning outcome of Pencak silat during the Covid-19 pandemic in 2020. The video with biomechanic analysis of Pencak silat was made using the Kinova application which aims to make it easier for students to learn the movements of a single artistic empty-handed category of Pencak silat. The main element of assessment is the correctness of movement, therefore students must memorize the moves and sequences correctly. This research method was experimental one group of pre-test and post-test design. The subjects involved in this research were 38 physical education students (age: M=20.11, SD=0.39; gender: 35 male and 3 female) of Universitas Islam 45 Bekasi, Indonesia. The data obtained were analyzed using the t-test. The results of the analysis show that the flipped classroom model integrated with the online learning platform influence the enhancement learning outcome of Pencak silat there was a significant (P ≤ 0.05). In addition, flipped classroom integrated with an online learning platform and video biomechanic analysis is the right formula to increase learning outcomes in Pencak silat.